Budi sejahtera practices in entrepreneurship - Zainudin, Dolhadi; Mhd. Sarif, Suhaimi; Ismail, Yusof (Kulliyyah of Economics and Management Sciences IIUM, 2021)
Budi Sejahtera combines two powerful terms in Islamic Malay culture, philosophy, ethics and social responsibility. Both values have been practiced in all aspects of life. Notably, Budi Sejahtera has been emphasized in entrepreneurship ventures. Budi Sejahtera has been apparent in decision making process. Budi Sejahtera values in entrepreneurship enable entrepreneurship ventures to make noble economic and social contributions to the human civilization.